ANALISIS PROBLEMATIKA GURU SENI BUDAYA (SENI MUSIK) DALAM MELAKSANAAN MATA PELAJARAN SENI BUDAYA DI SMA NEGERI KOTA PONTIANAK, KALIMANTAN BARAT - Nurmila Sari Djau (Indonesian Journal of Basic Education, 2019)
Analysis of the problems of the Cultural Arts teacher in the field of Music Arts is motivated by the curiosity of researchers to describe the problems faced by the Cultural Arts teacher in the field of Music and Arts in carrying out learning. The purpose of this study is to describe the problems faced by the teacher and the strategies that the teacher undertakes in overcoming the problem. This study uses a qualitative method, with the subject of the study being the Arts and Culture teacher with a background in Music Arts, totaling six people. Data collection is done by observation, interviews, and documentation. The results of this study are the problems faced by teachers, namely first determining other art fields that must be taught, difficulties in compiling learning planning devices, determining objectives and learning material, related to other art fields that must be taught. Secondly, the understanding and artistic ability of students who are different in class, resulting in teacher difficulties in conducting assessments. The strategy is for the teacher to take part in training and find information related to the preparation of planning tools, and to study the manual independently in order to teach other sub-fields of art. Second, teachers vary the learning methods, and use assessment techniques that are appropriate for students who have insights or abilities that are perceived as lacking in Art and Culture subjects